Psychological Experience of Juvenile Offenders in Correctional Institutions: A Systematic Review Of Qualitative Studies - Juliana, Jesika; Hutagalung, Fonny Dameaty; Nor, Azmawaty Mohamad (Journal of Population and Social Studies [JPSS], 2024)
Juvenile delinquency is at a worrisome rate in every part of the world. The juvenile offenders themselves are in a vulnerable period of development while also living in the difficult situation of detainment. However, challenges that juvenile offenders face in correctional institutions, how they construct their reality about detainment as well as their mental health needs have not been widely addressed. Research on juvenile offenders’ psychological experiences is not sufficiently documented and expressed. Hence, much less attention or programs were directed to address these obstacles. This review aims to present the psychological experience of juvenile offenders in correctional institutions. The systematic review examined qualitative studies over a 10-year period that were published between 2012 and 2022 from five databases, resulting in 16 articles mostly indexed in SCOPUS. The study utilized the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework and the narrative synthesis approach. Moreover, the findings provide empirical evidence that juvenile offenders’ psychological experiences (i.e., negative and positive emotions) are evident throughout their detainment, and interaction with staff and peers is crucial in defining it. Therefore, some of the challenges of living in correctional institutions include the feeling of boredom, strict regulations, and lack of care. Hence, education on adaptive coping, expanded vocational opportunities, and programs providing warmth, safety, and positive environments are crucial to rehabilitating offenders.